MEMBANGUN KEUNGGULAN BERSAING MELALUI MANAJEMEN SUMBERDAYA MANUSIA - Samsuni Samsuni (CV. ADIBA AISHA AMIRA, 2025)
At globalization era, company has given on to change of information current, technological and commerce which so quickly penetrate region a state. Every activity of business shall the change merespon ably manajerial and technical in the form of program is transfer of human resource development and technology. So that highly competitive company, hence human resource development program require to be improved, pass program analyse work, rekrutmen, selection, orient, development and training and career development, so that yield preeminent human resource ready to compete in globalization era.